Tree species diversity and stumpage valuation of coastal hill forest in Perak, Malaysia - Sholeh, Ghollasimood; Ibrahim, Faridah Hanum; Abd. Ghani, Awang Noor (Forestry Department Peninsular Malaysia, 2013)
Economic value and species diversity of a coastal hill forest in Sungai Pinang Permanent Forest Reserve, Pulau Pangkor, Perak were determined based on the data from five 1-hectare plots. All stems with a diameter at breast height (DBH)≥ 5cm were enumerated and identified. EstimateS was used to compute estimators of species diversity and richness. Stand density was 664 trees/ha and the total stumpage value per hectare was MYR 94, 541 with Dipterocarpaceae contributing the highest stumpage value.